Protecting the rights of women in the ESCWA region through the proper use of UN resolutions and international protocols on war and armed conflict - Mallat, Chibli (United Nations, 2009)
"This study examines international human rights instruments and mechanisms related to the protection of the rights of women living in conflict situations and their relevance and applicability in the region of the Economic and Social Commission for Western Asia (ESCWA). It also identifies and examines the physical, economic, social, legal and other challenges facing women living in conflict situations; and makes recommendations to ESCWA member countries and the international community on the development of policies and programmes aimed at protecting the rights of women in conflict situations."-- Executive summary.